Design Optimization of Bulk Piezoelectric Acceleration Sensor for Enhanced Performance - Min-Ku Lee; Seung-Ho Han; Kyu-Hyun Park; Jin-Ju Park; Whung-Whoe Kim; Won-Ju Hwang; Gyoung-Ja Lee (Sensors, 2019)
While seeking to achieve high performances of a bulk piezoelectric acceleration sensor, we investigated the behavior of the design variables of the sensor components and optimized the sensor design using a numerical simulation based on piezoelectric analysis and metamodeling. The optimized results demonstrated that there was an exponential dependency in the trade-off relation between two performance indicators, the electric voltage and the resonant frequency, as induced by the design characteristics of the sensor. Among the design variables, a decrease in the base height and epoxy thickness and an increase in the piezo element’s inner diameter had a positive effect on two performances, while the head dimensions (diameter and height) exhibited the opposite effect on them. The optimal sensor designs are proposed within the valid range of resonant frequency (25−47.5 kHz). Our redesign of a commercial reference sensor improved the resonant frequency by 13.2% and the electric voltage by 46.1%.